Determination of Catechin Content in Green and Black Tea (Camellia sinensis L.) by UV-Vis Spectrophotometric Method - Nafisah, Umi; Dewi, Aptika Oktaviana Trisna; Lulu, Anes Aisna Hana (Fakultas Farmasi, Universitas Mulawarman, Samarinda, Indonesia, 2024)
Tea is one of the most commonly consumed beverages around the world. The chemical compounds contained in tea have a good effect on health because they contain polyphenolic compounds, catechins. This study examined the catechin compound content of black tea and green tea from Karanganyar (A) and Malang (B). This research aims to determine the differences in catechin levels in black and green tea types in Malang, East Java, and Karanganyar, Central Java plantations. The research method used was experimental. Identification of catechin content was done using UV-Vis Spectrophotometry method. Tea is extracted by brewing, 4 grams of green tea is brewed using distilled water for 6 minutes, while 5.6 grams of black tea is brewed using distilled water for 10 minutes with the comparison used is pure catechin solution. The results obtained for green tea Karanganyar (A) had a catechin content of 3.61±0.083%, green tea Malang (B) had a level of 2.97±0.037%, black tea Karanganyar (A) had a level of 3.14±0.065%, and black tea Malang (B) had a level of 1.60±0.009%. It is concluded that the catechin content of green tea is higher than black tea, and of the two samples, the high catechin content comes from Karanganyar (A). Keywords: catechins, green tea, black tea, malang, karanganyar